Table of Content - - (Journal of agricultural, environmental and veterinary sciences, 2025)
Table of Content: • Camel treatment through ages: A comparative study in Veterinary Medicine Prof. Mohamed Mostafa Seif • Review: Curry leaves and their role in naturally preserving meat proteins and meat products Asst-Prof. Lina S. Mohammed ,Asst-Prof. Alia Z. Hashem , Asst-Prof. Mohammed A. Salman • Investigation of Listeria monocytogenes in Meat of Broilers at The Northwestern Region of Syria Alaa Aldin Sobaia Alrahil , Prof. Fouad Hamad Al-Daoud • Nanotechnology and its Role in the Advancement of Horticultural Crops: A Scientific Article Asst-Prof. Fatin H. Al-Dulaimi , Prof. Mohammed A. H. Al-Najjar , Prof. Sukeyna. A. Aliwy, Prof. Wasen F. Fadel • Spatial Suitability of Harvesting Floodwater in The King Suleiman bin Abdelaziz’s Royal Reserve by Using GIS "Wadi Tawarn as a Model" Ms. Norah Mashaan Aid, Dr. Ummhani Idris Ahmed • Evaluation of pollination of date palm trees of the Halawi variety with pollen of the Canary and green Ghanamy date palms on productivity and chemical components of fruits Prof. Muntaha Abdul Zahra Ati, Asst-Prof. Abdul Samad A.Abdullah • Sustainable Valorization of Olive Oil By-products for Food Applications: Mini Review Ms. Ohoud Hussin Almasaudi, Dr. Asmahan Azhari ,Prof. Mohamed Gadallah Elsayed Gadallah